Telesounding, A Method of Wide Swathe Depth Measurement - Stubbs, A. R.; McCartney, B. S.; Legg, J. G. (The International Hydrographic Review, 2015)
Telesounding is the name given to wide swathe measurement of sea-bed depths. The method described here is based on using a relatively simple side-scan sonar system having multiple beams. The principles of operation are discussed and the main sources of error shown to be sound refraction and transducer roll instability. Experimental versions have been built, tested and operated, examples of the records and analyses being presented. An immediate and permanent record is obtained which can be interpreted topographically by eye. Depths can be measured out to ranges between five and ten times the water depth, with errors generally less than 2% of the water depth. Although coverage o f the swathe with soundings is not uniform and the high data rate may present problems, the benefits include a twenty-fold saving of ship time. The method has applications in marine geology and, with development, for hydrographic surveys.